DIFFERENTIAL EQUATION TO EVOLUTIONS OF THE SCATTERING MATRIX - A. I. Kozlov; V. Yu. Maslov (Научный вестник МГТУ ГА, 2016)
The characteristics of object scattering matrix are analyzed. The system of differential equations is obtained. It correlates (links) changes in ratio magnitude of Grave’s own matrix values with the corresponding changes in matrix elements the magnitude scattering.